Reflections of well-being: navigating body image, chronic energy deficiency, and nutritional intake among urban and rural adolescents - Yulia, Cica; Rosdiana, Delita Septia; Muktiarni, M.; Sari, Desyane Ramadhina (Frontiers in Nutrition, 2024)
Background: Adolescent growth and development is a period of very specific nutritional problems. As a result of poor growth and development, 36.3% of adolescents in Indonesia are at risk of developing CED. The purpose of this study was to determine the description of body image, the incidence of Chronic Energy Deficiency (CED), and nutritional intake in adolescents in urban and rural areas. Methods: This study used a descriptive quantitative design with a cross-sectional study conducted in Bandung and Sumedang on 387 adolescents aged 13-15 years. The instruments used in this study were body image questionnaire Figure Rating Scale (FRS) method¸ 2 x 24-hour food recall, and anthropometry for Measuring mid upper arm circumference (MUAC).Results: Results of this study showed that more than half of adolescents in urban (54.0%) and rural areas (61.7%) were at risk of CED, had negative body image perceptions in urban (69.1%) and rural areas (62.3%), and underconsumption of macronutrients in both urban and rural adolescents.Most adolescents in urban and rural areas still consume less energy, carbohydrates, and protein. Perceived body image and nutrient intake contribute to the incidence of CED in adolescents.